PENGUATAN INTERPRETASI YURIDIS TERHADAP PASAL 135 UNDANG-UNDANG NOMOR 6 TAHUN 2011 DALAM PENANGANAN KASUS PERKAWINAN SEMU - Scientia Ulfa Gakenti (STKIP Subang, 2026)
Article 135 of Law No. 6 of 2011 on Immigration sets forth criminal penalties specifically designed to combat the practice of sham marriages entered into by foreign nationals for the purpose of obtaining immigration documents or citizenship of the Republic of Indonesia. This provision establishes cumulative criminal liability, namely imprisonment for a maximum of five years and a fine of up to Rp500,000,000.00 for any person who enters into a mixed marriage not based on a genuine intention to marry, but solely to obtain immigration documents or Indonesian citizenship. Although this normative basis is explicitly in place, immigration law enforcement officials at the operational level often show hesitation in applying Article 135, due to normative ambiguity in determining the “non-genuine” nature of a marriage, the absence of a regulatory definition regarding the indicators for proving a sham marriage, as well as jurisdictional uncertainties arising from the intersection of immigration law with civil and religious family law. This study employs a normative legal research method that combines statutory, conceptual, and case-based approaches to examine the legal construction of Article 135, analyze its elements of proof in relation to sham marriages, and formulate an interpretive framework capable of guiding immigration officials in their operational duties. Based on empirical statistical data on enforcement actions by the Directorate General of Immigration for 2023–2025, comparative jurisprudence from the European Union and Southeast Asian jurisdictions, as well as documented case studies of Indonesian immigration law enforcement practices, this study argues that Article 135 has sufficient normative scope when interpreted teleologically, systematically, and extensively to cover the entire spectrum of sham marriage acts. The study concludes with concrete recommendations for regulation and interpretation, including a proposed Circular Letter from the Director General of Immigration and a standard evidence checklist for field officers..